The cost impact of unselective vs selective MammaPrint testing in early-stage breast cancer in Southern Africa - Myburgh, Ettienne J.; de Jager, Josephus J.; Murray, Elizabeth; Grant, Kathleen A.; Kotze, Maritha J.; de Klerk, Hermanus (Breast (Edinburgh), 2021)
MammaPrint (MP) has been applied in South Africa (SA) for decision-making in early-stage hormone receptor-positive breast cancer since 2006. The cost-impact of MP in SA has not been assessed. To assess different MP testing strategies for cost-minimization in early-stage breast carcinoma using a funder perspective. Clinico-pathologic information was extracted from a prospectively collected database. Clinical risk stratification was done using Adjuvant Online! (AOL) and the Predict V2.1 algorithm (www.predict.nhs.uk). An unselected MP testing strategy was compared to a selective strategy, testing only clinically high risk (cHigh) patients. Excluding human epidermal growth factor receptor-2 positive tumours, the costs for chemotherapy treatment and MP using funding data were used to evaluate the financial impact of these strategies. In 583 patients with 601 tumours, 52% were clinically low risk (cLow) (AOL) while the average Predict 10-year survival with chemotherapy was 2.9%. MP correlated strongly with Predict and 318 (60%) patients were MP low risk. Unselective testing allowed omission of chemotherapy in 44 (8.4%) patients but escalated cost by 57.7%. Using a selective testing strategy, only 251 would be tested, de-escalating treatment in 138 (55%) and reducing cost by 19.5%. Considering a Predict value up to 3.2% as cHigh, cost would be up to 7.3% (p = 0.0467) lower with a selective testing strategy. MP allowed reduction in the use of adjuvant chemotherapy. Unselective use of MP increases overall costs. A selective testing strategy through clinical risk stratification using AOL/Predict results in substantial cost saving. •Current clinical application of MammaPrint in early breast cancer in South Africa results in the testing of a large percentage of clinically low risk patients.•When expensive assays, is used in this (unselected) manner, it results in reduced use of chemotherapy, but the total direct cost is increased.•A selective testing strategy could result in substantial cost savings.